Leigjendavandinn : the tenant problem in geothermal leasing - Christopher Mathews 1961- (2017)
Iceland is heavily reliant on the efficient use of geothermal energy. Two-thirds of the nation’s current energy needs are met by geothermal resources, and if properly utilized geothermal energy can power Iceland for centuries to come. The division between ownership and control of the resources has caused concern among Icelandic policymakers that private companies with temporary rights to use geothermal resources may focus on short-term exploitation to the detriment of the long-term public interest. This issue is called leigjendavandinn, the tenant problem. Iceland developed a statutory solution for the tenant problem in 2008; but European authorities contend the law violates international agreements and have demanded it be changed. This paper looks at geothermal power and the dispute over Iceland’s answer to the tenant problem, and proposes an alternative approach to the problem consistent with both Icelandic and European law. Ísland er mjög háð skilvirkri notkun á jarðhita. Tveir-þriðju af orkuþörfum landsins er nú mætt með jarðhita, og ef auðlindin er nýtt á skilvirkan hátt getur hún knúið landið í aldaraðir. Mögulegt lagalegt bil milli eignar og stjórnar auðlindarinnar hefur valdið því að íslensk stjórnvöld eru farin að hafa áhyggjur af því að fyrirtæki með tímabundinn nýtingarétt á auðlindinni muni einblína á skammtíma nýtingu sem muni skaða langtíma hagmunum almennings. Þessi vandi er kallaður leigjendavandinn (e. the tenant problem). Ísland þróaði lögboðna lausn við leigjendavandanum árið 2008, en Evrópsk stjórnvöld telja íslensku lögin vera brot á alþjóða sáttmálum og krefjast þess að þeim verði breytt. Þessi rannsókn skoðar jarðhita og deiluna um lausn Íslands á leigjendavandanum, og leggur fram aðra nálgun á vandanum sem er í samræmi við bæði íslensk og evrópsk lög. Leitarorð: jarðhiti, leiga, leigjandi, stefna, leigjendavandinn